Analisis Penerapan Green Habits Untuk Membentuk Karakter Peduli Lingkungan Siswa di SDN 2 Tanjungpuro - Sarmila Annisa; Lina Erviana; Afid Burhanuddin (Scholarly Journal of Elementary School, 2026)
The formation of students’ environmental care character can be realized through the implementation of green habits. Green habits are positive behaviors carried out consciously to foster an attitude of caring for the environment in schools. This study aims to examine the implementation of green habits in shaping students’ environmental care character at SDN 2 Tanjungpuro, as well as to identify the supporting and inhibiting factors in its implementation. This research uses a qualitative descriptive approach with a case study design. Data were collected through observation, interviews, and documentation. The data analysis technique employed the Miles and Huberman model, which includes data collection, data reduction, data display, and conclusion drawing. The results show that the implementation of green habits is carried out in daily activities through various routines. The implementation is supported by adequate facilities and infrastructure, role modeling from school members, and active student participation. However, there are still obstacles, such as students’ inconsistent awareness and the influence of peers.